1972
DOI: 10.1037/h0033008
|View full text |Cite
|
Sign up to set email alerts
|

Sex typing in nursery school children's play interests.

Abstract: The authors investigated (a) different components of sex typing in play interests, (b) a potential masculine bias in Brown's It Scale for Children, and (c) selected social learning concepts of sex-role development. Subjects were 32 white, 4-year-old, upper-class children and 56 of their parents. To measure sex-role orientation, preference, and adoption, respectively, the children were given an "imaginary It" and a "you" version of the It Scale for Children and were scored at home on play interests. On all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
34
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 11 publications
8
34
0
Order By: Relevance
“…This finding is in accordance with previous literature that found that boys from many countries are more stereotyped in their preferences than girls (e.g., Eisenberg et al, 1982;Fling & Manosevitz, 1972;Turner et al, 1993). These findings may be explained by the greater social pressure for boys to exhibit gender typical behavior and to avoid gender atypical behavior at an earlier age (Fling & Manosevitz, 1972;Maccoby & Jacklin, 1987).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is in accordance with previous literature that found that boys from many countries are more stereotyped in their preferences than girls (e.g., Eisenberg et al, 1982;Fling & Manosevitz, 1972;Turner et al, 1993). These findings may be explained by the greater social pressure for boys to exhibit gender typical behavior and to avoid gender atypical behavior at an earlier age (Fling & Manosevitz, 1972;Maccoby & Jacklin, 1987).…”
Section: Discussionsupporting
confidence: 93%
“…For example, boys are more stereotyped than girls in their choice of child and adult sex roles (Edelbrock & Sugawara, 1978;Turner et al, 1993), play style (Eisenberg, Murray, & Hite, 1982;Fling & Manosevitz, 1972), friendship appraisals (Zucker, Wilson-Smith, Kurita, & Stern, 1995), and toy preferences (Turner et al, 1993). Like gender, gender schematicity is thought to influence gender typical behaviors in general (e.g., gender transformational errors and gender-relevant memories; Bradbard & Endsley, 1983;Bradbard, Martin, Endsley, & Halverson, 1986) and toy preferences in particular.…”
Section: Introductionmentioning
confidence: 96%
“…However, parents have traditionally responded to their sons and daughters in quite different ways. Sons have been more often encouraged to participate in more active activities while females have been more often reinforced for engaging in sedentary activities (Fling & Manosevitz, 1972;Lansky, 1967;Lever, 1976;Saegert & Hart, 1977). Thus, it appears that parents hold different ideas about the importance of sport involvement for their sons and daughters.…”
mentioning
confidence: 97%
“…Since the male role has been narrowly defined, the male transgresses more than the female and receives more negative responses from significant others. This hypothesis was supported by Lansky (1967) and Fling and Manosevitz (1972). Lansky used hypothetical situations to test parental reactions to sex-typed behavior.…”
mentioning
confidence: 81%